2021
DOI: 10.1111/jzs.12561
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation and phylogeny of Doto (Nudibranchia: Dotidae) from the Northeast Atlantic, with a discussion on food specialization

Abstract: The nudibranch genus Doto is taxonomically problematic in particular, and some species are described on the notion of strict monophagy. Here we perform species delimitation on NE Atlantic species, as well as placing them phylogenetically, using two markers: the mitochondrial COI and the nuclear H3. We also study the morphology of the species including radular ultrastructure and review food specificity. Specimens were first divided into potential species using ABDG on both markers, these groups were used as inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Moreover, since 2010, several international collaborative projects on nudibranch molluscs have been implemented around the Norwegian Gulen Dive Resort at Sognefjorden with several significant outcomes. These collaborative works have added significantly to our understanding of the taxonomy of several major nudibranch groups and include the descriptions of new species of Dendronotacea, Trinchesiidae, and Eubranchidae (Korshunova et al, 2017c(Korshunova et al, , 2019(Korshunova et al, , 2020a(Korshunova et al, , 2020bMartinsson et al, 2021) as well as a large monograph on the taxonomy of aeolidacean nudibranchs (Korshunova et al, 2017b). In addition, several recent studies from southern Norway have added to the knowledge on nudibranchs in Norway (Evertsen and Bakken, 2013;Sørensen et al, 2020;Neuhaus et al, 2021).…”
Section: Culminating In Hismentioning
confidence: 99%
“…Moreover, since 2010, several international collaborative projects on nudibranch molluscs have been implemented around the Norwegian Gulen Dive Resort at Sognefjorden with several significant outcomes. These collaborative works have added significantly to our understanding of the taxonomy of several major nudibranch groups and include the descriptions of new species of Dendronotacea, Trinchesiidae, and Eubranchidae (Korshunova et al, 2017c(Korshunova et al, , 2019(Korshunova et al, , 2020a(Korshunova et al, , 2020bMartinsson et al, 2021) as well as a large monograph on the taxonomy of aeolidacean nudibranchs (Korshunova et al, 2017b). In addition, several recent studies from southern Norway have added to the knowledge on nudibranchs in Norway (Evertsen and Bakken, 2013;Sørensen et al, 2020;Neuhaus et al, 2021).…”
Section: Culminating In Hismentioning
confidence: 99%
“…Preliminary studies of Eubranchus exiguus in the Barents Sea indicated some variation of the external morphology of specimens. Based on experience with other boreal cladobranch species (Ekimova et al, 2015(Ekimova et al, , 2022aKorshunova et al, 2020;Sørensen et al, 2020;Martinsson et al, 2021) these differences may be interpreted either as intraspecific variation or as interspecific differences. Different researchers argued that it is necessary to be very careful with morphological analysis.…”
Section: Introductionmentioning
confidence: 99%